QUALITY CONTROL OF PLANTATIONS TIMBER, AN ALTERNATIVE TO ENCOURAGE TREE GROWING OF TIMBER FOREST SPECIES, CASE STUDY OF Cedrelinga catenaeformis TORNILLO - BALUARTE VÁSQUEZ, Juan (2019)
In the present study the optimal turn of use of the trees of "tornillo" plantations has been compared based on the annual average increments and the current annual increases in volume of 1349 trees, versus the results of the probable uses of the wood of plantations of the same species, based on the study of the physical, mechanical and workability properties of wood of different ages, located in the Jenaro Herrera Research Center - CIJH. The first study shows that the optimal turn of silvicultural use of "tornillo" occurs at the age of 13 years, when the wood of this still does not have sufficient maturity compared to wood from natural forests. Alternatively, the study of the physical, mechanical and workability properties, recommends the use of "tornillo" wood from the age of 15, considerably reducing the period of time for the log to reach maturity, which allows inferring that the "tornillo" wood can be used before the wood matures. This information was complemented with second-source studies on the economic benefits and carbon estimation of aerial "tornillo" biomass in plantations. This study aims to help encourage the cultivation of trees by making the case study of this species available to those interested and, on the other hand, recommendations are made to promote policies for the cultivation and use of wood from plantations.